2020
DOI: 10.1213/ane.0000000000004967
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the Combination of Propofol and Ketamine for Procedural Sedation/Anesthesia in the Pediatric Population: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Drugs such as propofol and ketamine are used alone or in combination to provide sedation for medical procedures in children. The purpose of this systematic review was to compare the safety and effectiveness of propofol and ketamine to other drug regimens. METHODS: We searched Medline, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Cochrane Database of Systematic Reviews (CDSR), Web of Science, and the grey literature (meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 50 publications
1
13
0
3
Order By: Relevance
“…In conclusion, even with a few articles mentioned in this study, ketofol has a short pathway to become the best pediatric procedure sedative outside the operating room, with data from Hayes et al 1 being confirmed by other good-quality articles. This article is extremely well-written and clear and concludes that using propofol with ketamine is safe, since you have in your hands appropriate resuscitation tools and are prepared to conduct the side effects, albeit rare, when you need to do this.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…In conclusion, even with a few articles mentioned in this study, ketofol has a short pathway to become the best pediatric procedure sedative outside the operating room, with data from Hayes et al 1 being confirmed by other good-quality articles. This article is extremely well-written and clear and concludes that using propofol with ketamine is safe, since you have in your hands appropriate resuscitation tools and are prepared to conduct the side effects, albeit rare, when you need to do this.…”
supporting
confidence: 61%
“…To the Editor, It was with great interest that I read the article by Hayes JA et al 1 , entitled "Safety and efficacy of the combination of propofol and ketamine for procedural sedation/anesthesia in the pediatric population: a systematic review and meta-analysis" in the present issue of Anesthesia & Analgesia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This may explained that propofol had effect on airway smooth muscle reflexes [ 31 ]. Previous researches in the pediatric did not demonstrate the relationship between side effects and propofol/ketamine [ 32 37 ]. Pain with intravenous administration is an adverse effect of propofol [ 38 41 ].…”
Section: Discussionmentioning
confidence: 98%